Hubungan Lama Menderita Dan KomplikasiDiabetes Melitus Dengan Kualitas Hidup PadaPasien Penderita Diabetes Melitus Di WilayahPuskesmas Gatak Sukoharjo - Jihan Restada, Ertana, Okti Sri P, S.Kep., Ns., M.Kep., Sp.KMB (2016)
Diabetes is a chronic disease caused by lack of insulin production by the pancreas or the circumstances in which the body can not use the insulin that is produced effectively characterized by hyperglycemia or raising blood sugar levels. Type 2 Diabetes Mellitus is a disease of hyperglycemia due to insulin insensitivity metabolic cells were marked by the rise in blood sugar due to a decrease in insulin secretion by pancreatic beta cells and insulin function or disorder of insulin resistance. Complications were obtained on a person for the duration of diabetes mellitus. Chronic Complications arise with the effect of increased blood glucose levels over a long period. These complications can lead in short span of one's life, one's limitations and the increasing economic burden for the client and his family, that so influenced the decline in the quality of life if they do not get proper treatment. This research is descriptive correlative (non-experimental) using a cross sectional study approach with the aim to determine the relationship long-suffering and complications of diabetes mellitus with quality of life in patients with DM. The sampling technique using simple random sampling by the sample is 89 people with diabetes mellitus in Regional Health Center Gatak, sampling using random sampling. While the research instrument using questioner DQLCTQ-R dengen number of 34 items. The result of the calculation of Pearson Chi-Square test of a long-suffering relationship with quality of life and the 2 values obtained 1,157 significance value (p-value) is greater than 0561 (alpha) = 0.05. The result of the calculation of Pearson Chi-Square test complications relationship with quality of life and the values obtained 2,935 significance value (p-value) is greater than 0.87 (alpha) = 0.05. Researchers hope that patients with diabetes more courage in leading a healthy life so that quality of life is maintained, especially in patients who have been exposed to chronic complications by maintaining a regular diet, avoiding stress and getting support from family.